The “One Mind, Two Aspects” Model of the Self: The Self Model and Self-Cultivation Theory of Chinese Buddhism - Wang, Kai (Frontiers in Psychology, 2021)
Constructing a self model with universal cultural adaptability is a common concern of cultural psychologists. These models can be divided into two types: one is the self model based on Western culture, represented by the self theory of Marsh, Cooley, Fitts, etc.; the other is the non-self model based on Eastern culture, represented by the Mandela model of Hwang Kwang Kuo and the Taiji model of Zhen Dong Wang. However, these models do not fully explain the self structure and development of Chinese people in the context of Chinese Buddhist culture. Based on the self theory of Chinese Buddhism and inspired by the famous Buddhist work Awakening of Faith in the Mahāyāna, this article constructs the “one mind, two aspects” self model. This model can not only properly represent the self structure of Chinese people in the context of Chinese Buddhism, but can also explain the self-cultivation process and the realm of practice of Chinese Buddhist believers, and thus has satisfactory cultural validity.